Below What Hemoglobin Concentration in Pregnancy is there an Increased Risk of Maternal or Fetal Adverse Effects? - NKWABONG, Elie; FOMULU, Joseph Nelson (Journal of Women's Reproductive Health, 2015)
Objectives: To identify the lowest hemoglobin concentration (Hb) associated with increased risk of materno-fetal complications. Material and methods: This cohort study was conducted in the Yaoundé University Teaching Hospital, Cameroon, from March 1st, 2011 to February 28th, 2013. Maternal and fetal outcomes among anemic women (AW) and non-anemic women (NW) were compared. Two hundred and twelve AW (booking Hb <10g/dl) without any chronic diseases, carrying singletons and 212 similar NW (Hb ≥11g/dl) were followed up. Main variables were booking and 36 weeks Hb, complications observed and birth weight (BW). Data were analyzed using SPSS 18.0. Fisher exact test and t-test were used for comparison. Level of significance was P<0.05. Results: Mean booking Hb was 8.9 ± 1.1 g/dl among AW against 11.7 ± 0.6 g/dl among NW (P<0.001). Complications of anemia in pregnancy in our series (low BW (RR 7, 95%CI 1.6-30.4), pre-eclampsia (RR 3.3, 95%CI 0.9-11.9) and premature delivery (RR 3, 95%CI 0.6-14.6)) occurred frequently when mean 36 weeks Hb was <9g/dl. Conclusion: Complications were significantly observed when mean Hb was persistently <9g/dl.
Keywords: Anemia in pregnancy- Hemoglobin concentration- Maternal complications- Fetal complications.